Implementation of the Laravel framework in student activity service management - Siti Sufaidah; Feriska Maharani; Munawarah Munawarah (NEWTON: Networking and Information Technology, 2026)
Student activity service management is an important aspect in supporting the development of potential, participation, and administration of student activities in the university environment. At KH. A. Wahab Hasbullah University, the process of managing activities such as Field Experience Practice (PPL), internships, Community Service Programs (KKN), graduation ceremonies, and graduation ceremonies is still done manually, generally through WhatsApp groups. This method has limitations in terms of information reach, data documentation, and service efficiency. Therefore, this study aims to design and build a web-based student activity service management information system using the Laravel framework. Laravel was chosen because it supports the development of structured, secure, and efficient web applications with a Model-View-Controller (MVC) approach. The development method used is Waterfall, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The results of this study are expected to produce a digital platform that can accelerate the process of delivering information, simplify activity registration, and support documentation and reporting of student activities in an integrated and real-time manner.